The beneficial pharmacological effects of Uncaria rhynchophylla in neurodegenerative diseases: focus on alkaloids - Chen, Leilei; Liu, Yingjuan; Xie, Junxia (Frontiers in Pharmacology, 2024)
With the intensification of aging population, the prevention or treatment of neurodegenerative diseases, such as Parkinson's disease and Alzheimer's disease, have drawn more and more attentions. As a long used traditional Chinese medicine, Uncaria rhynchophylla (Miq.) Jacks., named Gouteng in Chinese, has been reported to have an effective neuroprotective role in neurodegenerative diseases. In this review, the beneficial pharmacological effects and signaling pathways of herbal formulas containing Uncaria rhynchophylla, especially major compounds identified from Uncaria rhynchophylla, including corynoxine B, corynoxine, rhynchophylline, isorhynchophylline, in neurodegenerative diseases were summarized, which not only provide an overview of Uncaria rhynchophylla for the prevention or treatment of neurodegenerative diseases, but also give some perspective to development new drugs from traditional Chinese medicine.